Exención de Impuestos para Equipos Agrícolas Selectos en Florida - Edward A. Evans (EDIS)
FE789 is the Spanish language version of FE715, “Florida Tax Exemption for Selected Farm Equipment,” a 3-page fact sheet by Edward A. Evans and part of the Tax Exemption for Agricultural Producers series. It describes the Power Farm Equipment Exemption Law, what farm equipment is included, and the procedure for obtaining the tax exemption. Includes references and a sample exemption certificate. Published by the UF Department of Food and Resource Economics, November 2008.